Development of animation video assistant teaching science courses in SD Negeri 056 Lamasariang - P. Purnama; P. Pattaufi; Nurhikmah H (Inovasi Kurikulum, 2023)
This development research focuses on making teaching materials in animated videos for science subjects at SDN 056 Lamasariang. Science subjects at SDN 056 Lamasariang. This research aims to improve learning effectiveness using an exciting visualization approach for students. This research uses technology and animation media to increase the involvement of students in the learning process, especially in learning process science subjects. Besides, it can help learners understand complex concepts that can be easily understood. The research method used is Research and Development with the ADDIE development model, which consists of 5 stages: analysis, design, development, implementation, and evaluation. The results showed that teaching materials based on animated videos are very effective in applying Class V science subjects, as seen from the acquisition of learning outcomes before (pretests) and after (posttest). The conclusion is that the results of developing teaching materials based on animated videos fulfill effective use in the learning process.